Controlling toughness of polymer-grafted nanoparticle composites for impact mitigation. Issue 2 (21st December 2021) - Chen, Shawn H.; Souna, Amanda J.; Stranick, Stephan J.; Jhalaria, Mayank; Kumar, Sanat K.; Soles, Christopher L.; Chan, Edwin P.
Abstract : Polymer toughness is typically dictated by the entanglement density. Here we demonstrate a new paradigm via polymer-grafted nanocomposites that couples segmental dynamics with the entanglement concept for enhanced toughness at high deformation rates. Abstract : Toughness in an entangled polymer network is typically controlled by the number of load-bearing topological constraints per unit volume. In this work, we demonstrate a new paradigm for controlling toughness at high deformation rates in a polymer-grafted nanoparticle composite system where the entanglement density increases with the molecular mass of the graft. An unexpected peak in the toughness is observed right before the system reaches full entanglement that cannot be described through the entanglement concept alone. Quasi-elastic neutron scattering reveals enhanced segmental fluctuations of the grafts on the picosecond time scale, which propagate out to nanoparticle fluctuations on the time scale 100s of seconds as evidenced by X-ray photon correlation spectroscopy. This surprising multi-scale dissipation process suggests a nanoparticle jamming–unjamming transition. The realization that segmental dynamics can be coupled with the entanglement concept for enhanced toughness at high rates of deformation is a novel insight with relevance to the design of composite materials.